PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM PENDIDIKAN KARAKTER DI SEKOLAH - Nufiar Syamsuddin (AZKIA : Jurnal Aktualisasi Pendidikan Islam, 2022)
Teachers have an important role in shaping the character of their students who are in formal and non-formal institutions. Teachers as one of the elements in education can influence students both directly and indirectly in forming a good character, especially since teachers are role models in the world of education, especially Islamic Religious Education Teachers in various educational institutions, both general and religious. Among the forms of character planting that are carried out are providing teachings, guidance, and giving encouragement and good examples in practicing the values of religious teachings, so related to the formation of children's character, teachers hold a central position, especially when children are in a school or madrasah environment. So that it is expected to form in the students' personal traits of good character, honesty, politeness, courage, hard work, responsibility and so on